Descripción de las capacidades para la innovación de una muestra de MiPymes de Acopi Valle Del Cauca (2023)
The main objective of this paper is to describe the innovation capacities of a sample of 31 MSMEs of the Colombian Association of Micro, Small and Medium Enterprises of (Acopi) Valle del Cauca. For this purpose, a study with descriptive scope was conducted. An instrument previously designed and validated was applied in the framework research of this work, composed of a questionnaire of 58 questions that took into account six innovation capacities such as: knowledge management, strategic management of innovation, potential, human capital, technological appropriation and relationship